Two-Year Follow Up after Autologous Matrix-induced Chondrogenesis (AMIC) in Patients with an Osteochondral Lesion of the Talus. Issue 4 (16th October 2019) - Anwander, Helen; Krause, Fabian Götz
Category: Sports Introduction/Purpose: The treatment of osteochondral lesions in the talus remains challenging. In recent years a promising technique, the autologous matrix-induced chondrogenesis (AMIC) has been described, a technique combining micro fracturing with application of a collagen matrix. The aim was to analyze the clinical follow up two years after surgery and define risk factors for inferior outcome. Methods: This prospective study included 16 consecutive patients, who underwent AMIC for an osteochondral lesion of the talus at our institution. We compared preoperative and at two years follow up the following clinical scores: AOFAS (American Orthopeadic foot and ankle score), FFI (foot functional index) and VAS (visual analogue scale) pain and satisfaction. Further, clinical scores at two years were correlated with BMI, age, gender and size and stage osteochondral lesion according to Hepple. Additionally outcome after primary AMIC and revision surgery was compared. Results: FFI increased from 50 ± 16 preoperative to 30 ± 24 at follow-up (p-value: 0.017). VAS pain increased from 5.6 ± 2.0 to 2.8 ± 2.7 (p-value: <0.001). AOFAS (67 ± 12 to 78 ± 21) and VAS satisfaction (7.2 ± 2.6 to 7.6 ± 2.8) change was not significant. AOFAS and FFI did not correlate with BMI, age, gender or size and grade of the osteochondral lesion. Patients with primary AMIC or revision surgery had a similar preoperative AOFAS (69 ± 11 versus 64 ± 14) and FFI (54 ± 14 versus 42 ± 17). At follow-up, patients with primary AMIC showed superior AOFAS (86 ± 11 versus 65 ± 27, p-value: 0.049) and FFI (17 ± 16 versus 52 ± 20; p- value: 0.001). Conclusion: Increased clinical outcome was found two years after AMIC in patients with talus cartilage lesion without previous surgery.